The moderating effects of wedding food costs on the late marriage among the Malay male adults / Mohd Salehuddin.Mohd Zahari and Mohd Salehuddin and Mohd Zulhilmi Suhaimi - Mohd Zahari, Mohd Salehuddin; Suhaimi, Mohd Zulhilmi (UiTM Press, 2016)
This paper reports on an empirical investigation into the causes of the late marriage among the Malay male adults in Malaysia. A descriptive research design using a quantitative approach was applied in this study, and the Malay male adults were the unit of analysis. The sample population was chosen among the selected single Malay male adults with age ranging from 30 to 40 years old. Three hundred and nineteen questionnaires were successfully collected. Through the application of descriptive and inferential statistics, some useful insights pertaining to the issue investigated significantly disclosed. Achieving higher than self-sustaining incomes, careers and advanced educational qualifications have given the weighty impacts, and the most remarkable finding is that food costs which include the wedding feast for the guests and other related amenities have the most significant influence on the late marriage among the Malay males’ adults in Malaysia. In other words, inability to provide the top expenses indeed the obvious cause. Such a phenomenon creates not only creates a burden to the male adults but given numerous consequences and implications to the community, society, and nation.